2016
DOI: 10.1021/acs.langmuir.6b03084
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Green Aerogels from Cross-Linked Hairy Nanocrystalline Cellulose and Modified Chitosan for Dye Removal

Abstract: A novel biopolymer-based aerogel was developed by freeze-drying a hydrogel, synthesized from cross-linking bifunctional hairy nanocrystalline cellulose and carboxymethylated chitosan through a Schiff base reaction. The nanocelluloses, bearing aldehyde and carboxylic acid groups, facilitated the cross-linking with chitosan through imine bond formation while providing negatively charged functional groups, and chitosan was modified to accommodate carboxylic acid. The potential of this bioaerogel in environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
115
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 49 publications
5
115
0
2
Order By: Relevance
“…demonstrated that highly porous chitosan foams with chelating amine functional groups can be a promising adsorbent material for anionic dyes from which the elution of dyes have been accomplished with alkaline treatment of the foams. Yang et al . reported reusable hybrid (cellulose and chitosan‐based) foams for the removal of cationic dyes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…demonstrated that highly porous chitosan foams with chelating amine functional groups can be a promising adsorbent material for anionic dyes from which the elution of dyes have been accomplished with alkaline treatment of the foams. Yang et al . reported reusable hybrid (cellulose and chitosan‐based) foams for the removal of cationic dyes.…”
Section: Introductionmentioning
confidence: 85%
“…In this case the dye molecules were desorbed by treating the hybrid foams in 0.1 m HCl, followed by washing with 0.1 m NaOH solution. Both of these studies, proved the excellent functional properties of foams for many cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A greater charge of the polymer network gives better water absorbency including saline solution. Due to the high swelling capacity and user‐friendliness, such superabsorbent materials have been extensively used in various applications such as biomedicine, drug delivery, heavy metals removal, personal care products and agriculture …”
Section: Introductionmentioning
confidence: 99%
“…Depending on the chemical treatment applied to the wood pulp, hairy nanoparticles can either have cationic charges, anionic charges, or no charges at all . The anionic form of this hairy nanocellulose is called electrosterically stabilized cellulose nanocrystals (ECNCs) and has been targeted for different uses such as heavy metal ions capture, biomimetic mineralization of calcium carbonate, and reusable green aerogels . In a previous work, both the dilute and the semi‐dilute regime of ECNC aqueous suspensions were studied.…”
Section: Introductionmentioning
confidence: 99%